Hybrid Mythology and Personal Nostalgia - Kim, Do-yeon (Auckland University of Technology, 2021)
I aim to produce a short-animated film consisting of both two-dimensional and three-dimensional components. The narrative will be based on hybrid myths, fables, and urban legends that I discovered as a child. Considering my personal experiences of moving to different countries (from New Zealand to Japan and Korea), reading various mythological tales helped me become familiar with significantly different cultural environments. Together, these experiences are significant as it relates to my sense of childhood nostalgia. I will research Greek, Korean and Japanese mythologies and incorporate their influences on symbolism which appears in my animated short film. Autobiographical experiences are used to drive the narrative of the storyline. This approach is supported with the use of anthropomorphism, through which my primary protagonist (based on an animal) is imbued with human-like qualities.
Keywords: Nostalgia; Mythology; Anthropomorphism; Animation